First description of larval stages of Aleochara pseudochrysorroa Caron, Mise & Klimaszewski, 2008 - Silva, Maycon R. Da; Zarbin, Paulo H. G. (Zootaxa, 2016)
Aleochara pseudochryssoroa is an abundant species near Centro Politécnico UFPR (Federal University of Paraná), Curitiba, Paraná, Brazil. This species can easily be collected in animal carcasses being an important fly regulator in this area. The adults of Aleochara prey on fly larvae, while the immature stages of Aleochara are parasitoids of fly pupae. The larvae studied here, were reared from adults of A. pseudochrysorroa collected in Curitiba, Paraná state, Brazil in animal carcasses. The immature specimens obtained were cleared and studied in glycerin in order to describe all immature stages. In this work, we describe and illustrate for the first time all larval instars of Aleochara pseudochryssoroa.